Money, credit, monetary policy and the business cycle in the euro area: What has changed since the crisis? - Domenico Giannone; Michele Lenza; Lucrezia Reichlin (European Central Bank (ECB), 2019)
This paper studies the relationship between the business cycle and financial intermediation in the euro area. We establish stylized facts and study their stability during the global financial crisis and the European sovereign debt crisis. Long-term interest rates have been exceptionally high and long-term loans and deposits exceptionally low since the Lehman collapse. Instead, short-term interest rates and short-term loans and deposits did not show abnormal dynamics in the course of the financial and sovereign debt crisis.
Keywords: E32; E51; E52; C32; C51; 330; Money; loans; non-financial corporations; monetary policy; euro area